1991
DOI: 10.1080/02772249109357674
|View full text |Cite
|
Sign up to set email alerts
|

Soil adsorption of 2,4‐D as affected by the clay mineralogy

Abstract: The adsorption of 2,4-D has been studied obtaining adsorption isotherms on 22 soils by the batch equilibration technique. Fitting the adsorption data to the Freundlich equation three adsorption capacity were calculated at low (Kf or Cs 1), medium (Cs4.5) and high (Cs 30) 2,4-D concentration. The adsorption capacity and intensity factors obtained in this study resulted in according with those reported by other authors. From the simple regression analysis between adsorption capacities and soil properties it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
4
9
1
Order By: Relevance
“…This is in agreement with the findings of previous studies in which soil organic carbon content was the primary factor influencing 2,4-D sorption in surface soil, both in field and laboratory experiments (Hermosin and Cornejo 1991;Mallawatantri and Mulla 1992;Johnson et al 1995;Farenhorst et al 2003). The A horizon had significantly greater capacity to sorb the herbicide relative to the B *, **, and *** denote P < 0.05, P < 0.01, and P < 0.001 level of significance, respectively, for correlations Ho: r = 0; Ha: r ≠ 0.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with the findings of previous studies in which soil organic carbon content was the primary factor influencing 2,4-D sorption in surface soil, both in field and laboratory experiments (Hermosin and Cornejo 1991;Mallawatantri and Mulla 1992;Johnson et al 1995;Farenhorst et al 2003). The A horizon had significantly greater capacity to sorb the herbicide relative to the B *, **, and *** denote P < 0.05, P < 0.01, and P < 0.001 level of significance, respectively, for correlations Ho: r = 0; Ha: r ≠ 0.…”
Section: Discussionsupporting
confidence: 93%
“…Sorption reactions between negatively charged clay and 2,4-D are theoretically possible via metal-ion bridges, but did not occur in this case because 2,4-D sorption decreased with increasing clay content in the A horizon. Although some clay minerals enhance the sorption of 2,4-D by soil (Hermosin and Cornejo 1991), montmorillonite clay, the dominant clay mineral present in Manitoba soils (Madden 1974), had no effect or a negative effect on 2,4-D sorption in several other studies (Hermosin and Cornejo 1993;Sannino et al 1997).…”
Section: Discussionmentioning
confidence: 90%
“…This is not surprising because soil organic carbon content is the primary factor influencing 2,4-D sorption (Reddy and Gambrell, 1987;Mallawatantri and Mulla, 1992;Hermosin and Cornejo, 1993;Johnson et al, 1995). In agreement with other studies (Hermosin and Cornejo, 1991), we also observed a negative linear relation between clay content and 2,4-D Kd. However, soil clay content had no significant influence on the sorption of 2,4-D in soil horizons of a conventional-tilled soil-landscape in Canada (Gaultier et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…The results indicated that there was variable decrease in adsorption with a maximum value of 53.8% on clay destructed soils showing the role played by clay in adsorption of hazardous organics ( Table 5). The results were in accordance with those obtained by Hermosin and Cornejo [37,38] and Cox et al [39,40] where the authors showed that clay fraction was responsible for sorption of many soil-applied pesticides.…”
Section: Adsorption Of Hazardous Organics On Claysupporting
confidence: 94%